Regulation of RPE65 expression in human retinal pigment epithelium cells - Olga A. Postnikova; Samuel William; Sheetal Uppal; Steven L. Bernstein; Eugenia Poliakov; Igor B. Rogozin; T. Michael Redmond (Scientific Reports)
Abstract The visual cycle is an important pathway in the retinal pigment epithelium (RPE) which regenerates 11-cis retinal chromophore for the retinal photoreceptors. The central enzyme in the visual cycle is RPE65 retinol isomerase. Expression of RPE65 mRNA and protein levels are significantly lower in RPE cell culture models when compared to native RPE. This limits the use of these models to study the visual cycle. To determine the main drivers of RPE65 regulation we compared the transcriptional profiles of native and cell culture models of RPE with various levels of RPE65 expression. We also compared the levels of RPE65 expression between ARPE-19 cells grown in media supplemented with 1 mM pyruvate (PYR) or 10 mM nicotinamide (NAM). In addition, we performed experiments directed at transcriptional and translational regulation of RPE65. We show that RPE65 mRNA and protein expression is significantly higher in NAM media grown cells than PYR cells. Transfection of cells with a variety of different vectors containing RPE65 ORFs with different promoters, codon optimization, IRES, 3’ UTRs, suggest that translational effects are less important than transcriptional status. Importantly, we found that feeding with rod outer segments (ROS) decreases RPE65 expression in NAM grown cells, suggesting that certain primary functions of the RPE (here, visual cycle and phagocytosis) are not positively linked. Analysis of differentially regulated microRNAs (miRs) provides a basis for this downregulation. It appears that the regulation of RPE65 expression in ARPE-19 cells, in particular, is multifactorial, involving primarily metabolic and transcriptional status of the cells, with translation of RPE65 mRNA playing a smaller role.